A green one-pot approach for mesoporous g-C3N4 nanosheets with in situ sodium doping for enhanced photocatalytic hydrogen evolution. (8th January 2019) - Shu, Zhu; Wang, Yang; Wang, Wenbin; Zhou, Jun; Li, Tiantian; Liu, Xueqin; Tan, Yigen; Zhao, Zhengliang
Abstract: Synchronous nano-structuring and element-doping of g-C3 N4 were realized via a green one-pot approach to improve its photocatalytic activity. Na-doped mesoporous g-C3 N4 nanosheets of ∼5 nm in thickness were facilely synthesized by calcining a mixture of dicyandiamide and sodium chloride. NaCl not only serves as a confining-reactor to confine the growth of g-C3 N4 into mesoporous nanosheets, but also acts as a sodium source for Na-doping. The nanosheets own greater specific surface area, stronger optical absorption and lower recombination of photo-induced electron-hole pairs than bulk g-C3 N4, and exhibit an excellent visible-light photocatalytic hydrogen evolution efficiency which is about 13 times that of bulk g-C3 N4 . Moreover, the thermostable and hydrosoluble NaCl is simply removed and recycled by water and then directly reused in a new synthesis, making the process to be environmental-friendly and sustainable. Graphical abstract: Green one-pot synthesis of mesoporous g-C3 N4 nanosheets with in situ Na-doping using NaCl as recyclable confining-reactor for efficient visible-light photocatalytic H2 evolution. Image 1 Highlights: Na-doped mesoporous g-C3 N4 nanosheets are synthesized in one pot. NaCl is used as a confining-reactor and only water is needed to remove it. The NaCl can be recycled and reused repeatedly to prepare nanosheets. The optimal sample gives a H2 evolution rate 12.9 times higher than bulk g-C3 N4 . Both nanosizing and Na-doping of g-C3 N4 contribute to the improved activity.